A study of the impact of staggered boards on corporate financialization: from the perspective of board governance - Cao, Chongyan; Zhang, Yutong (Frontiers in Psychology, 2024)
Introduction The objective of this study is to assess the influence of staggered boards on corporate financialization and the role that incentive and supervision mechanisms play in this process. Methods We employ a total of 20,647 panel data samples of Chinese A-share listed companies over the period 2011-2020 to empirically test the impact of staggered boards on corporate financialization in the Chinese context. Results The results indicate that implementing staggered boards significantly increases levels of corporate financialization. On the one hand, the implementation of a staggered board structure can exacerbate the speculative mindset and profit-driven behavior among board members, leading management to prioritize financial investments for personal gain. On the other hand, a staggered board system may also amplify managerial laziness, potentially incentivizing them to rely heavily on financial investments in order to swiftly achieve performance targets with minimal effort. Furthermore, both managerial ownership and audit supervision are found to be critical factors in mitigating this positive impact and preventing excessive financial investment behavior. Discussion This paper offers guidance on comprehending the applicability of staggered board provisions and mitigating financial risks in enterprises.